Omega-3 Fatty Acids for the Prevention of Recurrent Symptomatic AF: Results of the FORWARD Trial - Vinall, Phil (MD Conference Express, 2012)
According to the results from the Randomized Trial to Assess Efficacy of PUFA for the Maintenance of Sinus Rhythm in Persistent Atrial Fibrillation [FORWARD; NCT00597220], pharmacological supplementation with n-3 polyunsaturated fatty acids (PUFA) does not reduce recurrent atrial fibrillation.